2015
DOI: 10.1002/ls.1302
|View full text |Cite
|
Sign up to set email alerts
|

The temperature and pressure dependence of viscosity and volume for two reference liquids

Abstract: The new quantitative elastohydrodynamics has resulted in rapid advances in understanding concentrated contact lubrication behaviour by employing real transport properties. A key component of this revolution has been the use of reference liquids. In this paper, two liquids, a triester and a perfluoropolyether, which are under consideration as possible viscosity standards are characterised to 1 GPa for conditions relevant to tribology. Two correlations are provided for interpolation and data smoothing, and an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(72 citation statements)
references
References 33 publications
6
66
0
Order By: Relevance
“…The experimental data reported by Barrette and Jordaan (2003), Mctigue and others (1985) and Jones and Chew (1983) clearly highlight that hydrostatic pressure causes polycrystalline ice to modify its rheology. This type of behavior is comparable to that found in many other materials where the viscosity can vary by a factor of as much as 10 10 % (Prusa and others (2012); Bair (2015)). Experimental data concerning glaciers and rock glaciers show appreciable variation of the viscosity with the depth, as shown in Figure 2 of Kannan and Rajagopal (2013).…”
Section: Resultssupporting
confidence: 88%
“…The experimental data reported by Barrette and Jordaan (2003), Mctigue and others (1985) and Jones and Chew (1983) clearly highlight that hydrostatic pressure causes polycrystalline ice to modify its rheology. This type of behavior is comparable to that found in many other materials where the viscosity can vary by a factor of as much as 10 10 % (Prusa and others (2012); Bair (2015)). Experimental data concerning glaciers and rock glaciers show appreciable variation of the viscosity with the depth, as shown in Figure 2 of Kannan and Rajagopal (2013).…”
Section: Resultssupporting
confidence: 88%
“…In Table 2, we list the source, temperature, and pressure range as well as the nominal uncertainties of the sets of density data at atmospheric pressure as well as highpressure density data for TOTM that can be found in the literature. Most of the results have been obtained using vibrating U-tube densitometers from Anton Paar with one set of data obtained by Bair 12 with a bellows volumometer and another by Bamgbade et al 22 using another variable volume cell. Bazile et al 24 U-tube densitometer and also by integration of their speed-ofsound measurements (see section 3.6).…”
Section: Thermophysical Properties Of Totmmentioning
confidence: 99%
“…Five viscosity measurement sets on compressed liquid TOTM have been reported by Diogo et al, 15,23 Bair, 12 Baled et al, 21 and Linẽira del Ri ́o et al 25 Diogo et al measured the viscosity of two lots, A 15 and B, 23 using a vibrating-wire viscometer. Baled et al 21 measured the viscosity of lot C of TOTM using a windowed, variable-volume, rolling ball viscometer.…”
Section: Thermophysical Properties Of Totmmentioning
confidence: 99%
“…On the other hand, it was found that film thickness ratio is sensitive to pressure-viscosity coefficient; simulations were done for three values (Table 3) in a range from 8.7 to 32.7 GPa −1 . It corresponds to the pressure-viscosity coefficient according definition in Equation (8) published by Bair [23]. It was shown that it is able precisely capture relation of viscosity on pressure necessary for film thickness formation in EHL contacts.…”
Section: Resultsmentioning
confidence: 99%
“…Film thickness was measured for steel on glass and steel on sapphire configurations with reference fluid tri (2-ethylhexyl) trimellitate (TOTM, Sigma-Aldrich, Darmstadt, Germany) as a lubricant. Rheological properties of this fluid were measured in [23]. Basic rheology parameters for test temperature are in Table 1.…”
Section: Film Thickness Measurementmentioning
confidence: 99%